Growth Performance of the Monsoon River Prawn Macrobrachium malcolmsonii on Formulated Feeds with Combinations of Pulses and Cereals along with Groundnut Oilcake and Soya Meal - and C. Seenivasan, P. Saravana Bhavan*, S. Radhakrishnan (Journal of Ecobiotechnology, 2011)
This study was conducted to categorize the growth performance of feeds formulated with combinations of pulses and cereals (horse gram and ragi, green gram and pearl millet, and cow gram and wheat) along with groundnut oilcake and soya meal on the post larvae (PL) of the monsoon river prawn, Macrobrachium malcolmsonii. This is to promote the inland aquaculture of this economically important species. Two types of feeds with different proportions of pulse and cereal (type-A: 25% pulse + 25% cereal; type-B: 40% pulse + 10% cereal) were prepared in each combination along with equal proportion of groundnut oil cake and soya meal (20% each). Tapioca flour (5%) and egg albumin (4%) were used as binding agents. Vitamin B-complex (1%) was also mixed. These feeds were fed to M. malcolmsonii PL for a period of 45 days. The efficacy of these feeds on growth performance and biochemical constituents were assessed. Commercially available standard Scampi feed was served as control. The overall influence of these feeds on growth, and concentrations of total protein, amino acid, carbohydrate and lipid of PL were found to be the best in scampi feed followed by the feed rich in pulse (type-B) and the feed with equal proportion of pulses and cereals (type-A). Among three combinations of pulses and cereals were tested, the feed formulated with cow gram and wheat showed the best overall performance, followed by green gram and pearl millet, and horse gram and ragi.Ã‚Â All the results were confirmed through paired sample t-test, DMRT, and two-way ANOVA. The survival rate was found to be better in formulated feeds fed PL when compared with control. It is assumed that the additive/ preservative added in the commercially available scampi feed may be the reason for the lower survival rate recorded. Moreover, the commercially available scampi feed is not always affordable to small farmers. Therefore, the farm made feeds with locally available commodities of pulses and cereals can be prepared and used in a sustainable manner for healthy promotion of Macrobrachium culture.